2015
DOI: 10.1177/1534508415571594
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Psychometric Evidence of the Behavioral and Emotional Screening System Teacher Rating Scale–Preschool

Abstract: The aim of this study was to provide psychometric evidence related to the Behavioral and Emotional Screening System Teacher Rating Scale–Preschool form’s (BESS TRS-P) ability to identify emerging problems in preschool children. Reliability and validity associated with screener scores were compared by analyzing teacher ratings of approximately 700 preschool children from 11 public schools. The BESS TRS-P provided high levels of internal consistency and inter-rater reliability among respondents. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…R. Reynolds & Kamphaus, 2004). The results of the two forms are comparable with reported significant correlations (Achenbach & Rescorla, 2001; Greer, DiStefano, Liu, & Cain, 2015).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…R. Reynolds & Kamphaus, 2004). The results of the two forms are comparable with reported significant correlations (Achenbach & Rescorla, 2001; Greer, DiStefano, Liu, & Cain, 2015).…”
Section: Methodssupporting
confidence: 88%
“…One standard deviation above the average t scores (i.e., significant t score > 60) indicated the existence of EBD (Achenbach & Rescorla, 2001; C. R. Reynolds & Kamphaus, 2004). The results of the two forms are comparable with reported significant correlations (Achenbach & Rescorla, 2001;Greer, DiStefano, Liu, & Cain, 2015).…”
Section: Instrumentationsupporting
confidence: 89%
“…It has been argued that interventions should be implemented as early as possible (Greer et al 2015;Guralnick et al 2007) to prevent long-term negative consequences. Therefore, it is imperative to know which approaches are preferred by younger students in primary schools.…”
Section: Future Researchmentioning
confidence: 99%
“…Higher screener scores were negatively related to kindergarten readiness (r = −.71) and receptive vocabulary (r = −.52), and positively related to the presence of social-emotional development problems (r = .46) (Dowdy et al, 2013). Furthermore, correlations between early school year BESS TRS-P scores and Student Support Team status at end of school year suggested that higher screener scores were related to an increased potential for referral (Greer et al, 2015).…”
Section: Instrumentationmentioning
confidence: 98%
“…Concurrent validity information is also provided in the BESS manual, with strong relations (.55 and higher) in expected directions. Two additional studies using empirical data found BESS TRS-P scores were strongly correlated with relevant outcomes (Dowdy, Chin, & Quirk, 2013;Greer, DiStefano, Liu, & Cain, 2015). Higher screener scores were negatively related to kindergarten readiness (r = −.71) and receptive vocabulary (r = −.52), and positively related to the presence of social-emotional development problems (r = .46) (Dowdy et al, 2013).…”
Section: Instrumentationmentioning
confidence: 98%